Place-Based Environmental Civic Science: Urban Students Using STEM for Public Good - Gallay, Erin; Flanagan, Constance; Parker, Betsy (Frontiers in Education, 2021)
In the United States, Black and Latinx students are underrepresented in STEM courses and careers due to a dearth of culturally relevant opportunities, which in turn are connected to broader issues of social justice. Place-based environmental civic science offers potential for addressing these issues by enabling students to apply their STEM learning to mitigate local environmental problems. By civic science we refer to science for the public good. In this paper, we report on a study in which we followed middle- and high-school science and math classes in urban schools serving racial/ethnic minoritized students as they engaged in an innovative contextualized curriculum – a place-based civic science model in which students work with STEM community partners to address environmental issues in their community. We draw from students’ open-ended reflections on what they learned from participating in the place-based environmental civic science projects that could help their communities. Thematic analyses of reflections collected from 291 students point to beliefs in the usefulness of science to effect community change. Students articulated the science they learned or used in the project, and how it could affect their community; they made references to real world applications of science in their project work and made links between STEM and civic contributions. In their own words, the majority of students noted ways that STEM was relevant to their communities now or in the future; in addition, a subset of students expressed changes in their thinking about how they personally could apply science to positively impact their communities and the ties between STEM and social justice. Analyses also point to a sense of confidence and purpose students gained from using STEM learning for their goals of community contribution. Results of this study suggest that focusing on local place as a foundation for students’ STEM learning and linking that learning to the civic contributions they can make, cultivates students’ perceptions of how they can use science to benefit their communities. Findings also suggest that engaging students in place-based civic science work provides effective foundations for nurturing STEM interest and addressing the underrepresentation of youth of color in STEM.